Graphene-Based Tunable Wideband Metamaterial Absorber With Polarization Insensitivity and Wide Incident Angle - Wang, Liansheng; Xia, Dongyan; Fu, Quanhong; Ding, Xueyong; Wang, Yuan (Frontiers in Physics, 2020)
A graphene-based tunable wideband metamaterial absorber with polarization insensitivity and wide incident angle is presented in this paper. The results show that the absorption is over 90% from 5 to 8 GHz when the Fermi level of graphene is 0.5 eV, and the absorption can be tuned by electrically changing the Fermi level of graphene. The mechanism of wideband and tunable absorption is explained by calculating the normalized input impedance and monitoring the surface current. Finally, the results adequately verify that the absorption of metamaterial absorber has the advantages of polarization insensitivity and wide incident angle. Thus, it holds great potential application value in many fields such as electromagnetic stealth, electromagnetic shielding, communication, and so on.